Angels on the Streets - Choi In-kyu; Kim Hak-seong; Kim Il-hae; Moon Yae-bong; Kim Shin-jae (The Past Unearthed, 2007)
Cruelly treated by one of the criminal gangs who exploit orphans and children living on the streets of Jong-ro in Seoul, Yong-gil is separated from his sister Myung-ja when he runs away. The young boy is taken in by Bang Seong-bin, a kindly man who has helped many children in a similar predicament, much to the despair of his wife who wonders where they are going to house them all. Seong-bin arranges with his brother-in-law Doctor Ahu to rent a larger place in the country and, with apparently no consideration for social services or concern about child labour laws, sets up a noodle workshop so that they can pay for their expenses. Initially finding the country dull after living on the city streets, the kids soon come to appreciate this new life - but for Yong-gil, it only reminds him of how difficult things must be for his sister. Problems arise however which reunite them, but also bring trouble to their door. Well made and performed with conviction by the cast, "Angels on the Streets" is for the most part great drama in the style of Ozu’s "Record of a Tenement Gentleman", De Sica’s "Shoeshine" and the Chinese classic "Street Angel" ... Having already been living under Japanese occupation before the Second World War, Korean filmmaking consequently shows characteristics that would come later in Italian neo-realism, but filmed while the country was at war and scripted by a Japanese writer, the heavier restrictions of censorship and propaganda placed on Korean filmmakers also makes its mark on Choi In-kyu’s 1941 film. [www.dvdtimes.co.uk]